Transformation of Basketball Academy Athlete Performance Evaluation Using Information Technology and the Weighted Product Method - Pahrizal; R Wisnu Prio Pamungkas; Fried Sinlae (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
Performance evaluation of basketball athletes at academies in Indonesia still largely relies on manual, subjective, and unintegrated assessment processes, leading to inconsistencies between evaluation periods. This study aims to design and develop a web-based information system for athlete performance evaluation at Bendella Basketball Court, Bekasi, using the Weighted Product (WP) algorithm. The system was developed following the Waterfall Software Development Life Cycle (SDLC) methodology, covering requirements analysis, system design, implementation with the Laravel framework, and testing. Eight evaluation criteria were established: shooting (20%), dribbling (15%), defense (15%), passing (10%), speed (10%), stamina (10%), discipline (10%), and teamwork (10%). The WP algorithm computes vector S and preference value V for each athlete, followed by threshold-based categorization into Junior Advance and Junior Basic categories. Testing on five sample athletes demonstrates that the system correctly ranks and categorizes athletes objectively. The Weighted Product method provides greater stability compared to Simple Additive Weighting (SAW) with a sensitivity change of only 0.01% versus 0.38%. This system supports coaches in making more accurate, consistent, and data-driven athlete evaluation decisions.